Saillance des îlots textuels dans un corpus de presse britannique sur le Brexit et conséquences interprétatives associées - Laure Cataldo (Anglophonia)
The purpose of this contribution is to examine, in a British press corpus of 90 articles dealing with Brexit, the segments inserted between inverted commas within the narrative speech of the journalist (called “îlots textuels” in French) and to highlight the interpretative effects underlying their use by the journalist. These fragments of other’s discourse, frequently used in media discourse, are explicitly marked as being other with quotation marks which signal the heterogeneity of the discourse. They make it possible to attract the reader’s attention, to make the speech stand out by clearly separating it from the journalist's speech. This clearly indicated borrowing of statements from another source, displayed as such, corresponds to a strategy of highlighting elements of discourse by the journalist, which may reflect a desire to collude with the reader. It also enables the journalists to distance themselves from the comments and point out the will not to endorse them, particularly when the content of the fragment refers to connotative expressions and violent and/or vulgar vocabulary. Over and above this distancing, the insertion of these salient fragments in the journalist’s speech can represent a means to express a position regarding the source of the segment or its content, and therefore present interpretative consequences that go beyond simple highlighting. It is therefore a real discursive tool available to the journalists to let their opinion shine through.